Prevalence and Phenotypic Detection of Carbapenem and Multi Drug Resistant of E. Coli in Urinary Tract Infection Patients in District Swat : Detection of Carbapenem and Multi Drug Resistant of E. coli - Noor, Uzma; Suliman, Muhammad; Shams, Husna; Sultan, Amir; Hassan Khan, Shah; Shazia, . (Pakistan Journal of Health Sciences, 2022)
Among prevalent infectious diseases, the most frequently occurring infections are the Urinary Tract Infections (UTIs) which predominantly occur in the community as well as in the hospital settings and are one of the main cause of morbidity and mortality worldwide. Objectives: To determine the frequency of MBL E. coli species in urine samples, antibiotic susceptibility pattern and the prevalence of MDR for E. coli. Methods: There were 200 urine samples obtained from Anwar clinical laboratory Saidu Sharif, District Swat, Pakistan. Samples of urine were obtained and then cultivated in selective media i.e. Cysteine Lactose Electrolyte Deficient Agar (CLED) and MacConkey Agar Plates. In traditional morphological and biochemical studies, isolates were identified. Results: Total 58 (29.6%) positive isolates were recovered from male while 116 (70.3%) urine specimens were positive from female patients, A total isolated bacteria were MBL positive including 36 (31.3%) isolated E. coli, Furthermore, in the total isolated species were identified as MDR positive in which 80 (69.5%) were E. coli, The most potent antibiotics found against bacteria were the highest for Meropenum (78.2%), Imepenum (73.9%), and Amikacin (26.0%) Cefuroxime (21.7%), respectively and Cefaclor (19.1%) were most sensitive while antibiotic mostly resistant showed. Conclusion: This study concludes that, the most prominent bacterial isolate in the urine samples was E. coli 115 (69.6%), Carbapenem resistance is frequently observed isolates of E. coli, which indicate that MBL phenotype should be regularly determined in clinical settings to prevent emerging Carbapenem resistance.